Seesaw Based Digital Learning to Increase Higher Order Thinking Skills of Basic School Students in The Pandemic Period - Hasanah, Uswatun; Zulela, M S (International Conference on Elementary Education, 2021)
The purpose of this study was to analyze the effectiveness of digital seesaw-based learning in improving students' higher-order thinking skills. This study uses Research and Development. The study procedure uses the dick and Carrey model which has ten stages. The instrument in this study used a questionnaire to determine the feasibility of the media in terms of expert validation and field testing and then used a test instrument to measure students' higher-order thinking skills. Evaluation is carried out in three stages; the first stage is expert judgment carried out by media and material experts. The step was evaluated by a small group of ten students. The test results state that digital teaching materials are suitable for use. To see the effectiveness of the product developed, the newest field group was followed by a total of 30 students at SDS Laboratory. Analysis of test results shows the difference in learning outcomes between pre-test and post-test. Judging from the average value, it shows that the digital teaching materials based on the seesaw developed are effectively used in improving student’s thinking skills of elementary school students. The novelty of this research includes the digital learning design developed by the researcher which is integrated with the aspects of high-level thinking skills of students and researchers combining several applications such as PowToon, phet, video scribe which are packaged in the seesaw platform. Of course, the results of this study can be a very interactive digital learning innovation and can increase student's higher-order thinking skills in the pandemic period.